2014
DOI: 10.1063/1.4865422
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and dielectric properties of Aurivillius phase Bi6Fe2Ti3−2xNbxCoxO18 (0 ≤ x ≤ 0.4)

Abstract: Articles you may be interested inMagnetic, dielectric, and magneto-dielectric properties of rare-earth-substituted Aurivillius phase Bi6Fe1.4Co0.6Ti3O18Two distinct dielectric relaxation mechanisms in the low-frequency range in Bi 5 Ti Nb W O 15 ceramics Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Therefore, attempting to synthesize room temperature multiferroic materials is a challenging task of materials science. Doping magnetic species into ferroelectric matrices is one of the most effective ways to obtain room temperature multiferroics, and thus has received much attention in the past few years [4][5][6][7][8][9][10][11][12][13]. Ferromagnetism was successfully introduced in the ferroelectric BaTiO 3 material by Fe doping, however, its ferroelectricity was suppressed simultaneously due to the decreased tetragonal distortion and the enhanced leakage current [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, attempting to synthesize room temperature multiferroic materials is a challenging task of materials science. Doping magnetic species into ferroelectric matrices is one of the most effective ways to obtain room temperature multiferroics, and thus has received much attention in the past few years [4][5][6][7][8][9][10][11][12][13]. Ferromagnetism was successfully introduced in the ferroelectric BaTiO 3 material by Fe doping, however, its ferroelectricity was suppressed simultaneously due to the decreased tetragonal distortion and the enhanced leakage current [4].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 By doping Co at Fe sites, Mao et al found that Bi 5 Fe 0.5 Co 0.5 Ti 3 O 15 presents a remarkable coexistence of the ferroelectricity and ferromagnetism above RT. 7 17,18 Therefore, inserting a magnetic unit into the Aurivillius phase may be an effective way to regulate the magnetic and magnetoelectric properties by modulating the interlayer distance, the number of perovskite-like layers, and the coupling between magnetic cations such as Fe 3þ , Co 3þ , and Mn 3þ . It is known that ferromagnetic material BiMnO 3 exhibits the magnetocapacitance effect arising from the inherent magnetoelectric coupling between the ferroelectric and ferromagnetic orders.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mutliferroic (MF) properties of the coexistence of magnetic, ferroelectric and/or ferroelastic orderings in one phase can be realized by inserting the typical MF BiFeO 3 phase into the isostructural Bi 4 Ti 3 O 12 BLFs, whose formula is expressed as Bi 4 Bi n-3 Ti 3 Fe n-3 O 3n+3 (n is an integer greater than or equal to 4, denoting the number of perovskite layer). More importantly, an associated magnetoelectric (ME) coupling between spin and dipolar orderings drives them to be qualified in the high-speed and low-power consumption multi-state memory, spintronics devices and even in photovoltaic cells56789101112131415. Nevertheless, the nature of antiferromagnetic ordering and weak ME coupling of Aurivillius MF phases restricts their prospects of the practical application67891011121314.…”
mentioning
confidence: 99%
“…More importantly, an associated magnetoelectric (ME) coupling between spin and dipolar orderings drives them to be qualified in the high-speed and low-power consumption multi-state memory, spintronics devices and even in photovoltaic cells56789101112131415. Nevertheless, the nature of antiferromagnetic ordering and weak ME coupling of Aurivillius MF phases restricts their prospects of the practical application67891011121314. Consequently, various routes including A/B site doping, interface and stress engineering were adopted to regulate the magnetic orderings and ME coupling567891011121314.…”
mentioning
confidence: 99%